1999
DOI: 10.1034/j.1399-0039.1999.530405.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II alleles in Japanese patients with inflammatory bowel disease

Abstract: The association of various HLA class II loci with Crohn's disease (CD) and ulcerative colitis (UC) has yet to be fully elucidated. To determine whether there is an association of HLA class II genes (DR, DQ and DP alleles) with inflammatory bowel disease (IBD), HLA class II genes for polymorphisms were analyzed at the DNA level in 111 patients with CD, 81 with UC and 525 healthy controls by the polymerase chain reaction-sequence specific oligonucleotide probe method. Allele and haplotype frequencies were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 0 publications
3
51
0
Order By: Relevance
“…In other serologic studies, the HLA class II DR1-DQ5 haplotype was found to be associated with CD in Caucasians [12,15,25]. Moreover, recent molecular analyses of the HLA class II genes in Japanese [16,23,24] and Caucasian populations [13,[26][27][28] (including the current study) demonstrated significant HLA class II allele and haplotype associations with IBD.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…In other serologic studies, the HLA class II DR1-DQ5 haplotype was found to be associated with CD in Caucasians [12,15,25]. Moreover, recent molecular analyses of the HLA class II genes in Japanese [16,23,24] and Caucasian populations [13,[26][27][28] (including the current study) demonstrated significant HLA class II allele and haplotype associations with IBD.…”
Section: Introductionsupporting
confidence: 65%
“…Two recent studies of Japanese CD patients, however, indicated a significant association with DQB1*0402 [16,23]. In those studies, DQB1*0402 was linked to DRB1*0410, which was also associated with CD.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations